PENGARUH PERTUMBUHAN EKONOMI, INDEKS PEMBANGUNAN MANUSIA, DAN PENGANGGURAN TERBUKA TERHADAP KEMISKINAN DI KALIMANTAN BARAT - B01111066, Laura Desiati (Jurnal Pembangunan dan Pemerataan, 2016)
The purpose of this study was to analyze the effect of economic growth, human development index, and unemployment on poverty in West Kalimantan. This research is a quantitative research using panel data, the data used in the form of time series (2009-2013) and data cross (14 regencies / cities in Kalimantan Barat). The data used in this research is secondary data obtained from the Central Statistics Agency and the journal as a supporter. The analytical method used is the method of multiple linear regression analysis with FEM methods used Eviews 6 software tools. The results showed that the variables of economic growth is not significant effect on poverty, minimum wage no significant effect on poverty, unemployment no significant effect on poverty. Based on these results, it is expected that the government of West Kalimantan should expand employment opportunities by making it easier to open a business license in order to work the greater the chance that a lot of manpower absorption which will have an impact on poverty figures. Improve services in education and health, and improve public infrastructure so that any activity in promoting economic growth running smoothly so that poverty can be overcome. Keywords: poverty, economic growth, human development index, and unemployment